José María Arancibia, Escritos de monjas. Monasterio Santa Catalina de Siena, Córdoba, Argentina. (Tucumán: Universidad del Norte Santo Tomás de Aquino, UNSTA, 2023), 551 pp. - Clissa, Karina (2024)
Fil: Clissa, Karina. Universidad Católica de Córdoba; Argentina